Identification of SKOR2 IgG as a novel biomarker of paraneoplastic neurologic syndrome - Rezk, Mohamed; Pittock, Sean J.; Kapadia, Ronak K.; Knight, Andrew M.; Guo, Yong; Gupta, Pranjal; LaFrance-Corey, Reghann G.; Zekeridou, Anastasia; McKeon, Andrew; Dasari, Surendra; Mills, John R.; Dubey, Divyanshu (Frontiers in Immunology, 2023)
Introduction: Development of new autoantigen discovery techniques, like programmable phage immunoprecipitation sequencing (PhIP-Seq) has accelerated discovery of neural specific autoantibodies. Herein, we report identification of a novel biomarker of paraneoplastic neurologic syndrome (PNS), Sloan-Kettering-Virus-Family-Transcriptional-Corepressor-2 (SKOR2)-IgG utilizing PhIP-Seq. We have also performed thorough clinical validation utilizing normal healthy and disease/cancer control samples. Methods: Stored specimens with unclassified staining at the junction of Purkinje cell and granule cell layers were analyzed by PhIP-Seq for putative autoantigen identification. The autoantigen was confirmed utilizing recombinant antigen expressing cell-based assay (CBA), western blotting, and tissue immunflourescence assay colocalization.Results: PhIP-Seq data revealed SKOR2 as the candidate autoantigen. The target antigen was confirmed by a recombinant SKOR-2 expressing CBA, cryosectioned mouse brain tissue immunflourescence assay colocalization with a commercial SKOR2-specific IgG and cell lysate western blot. Furthermore, IgG from both patients' samples colocalized with a commercial SKOR2-specific IgG on cryosections of mouse brain. Both the SKOR2 IgG positive patients had central nervous system involvement, one presenting with encephalitis and seizures (patient 1) and the other with cognitive dysfunction, spastic ataxia, dysarthria, dysphagia, and pseudobulbar affect (patient 2). They had a refractory progressive course and were diagnosed of adenocarcinoma (patient 1: lung, patient 2: gall bladder). Sera from adenocarcinoma patients without PNS (n=30) tested for SKOR2-IgG were negative.Discussion: SKOR2 IgG represents a novel biomarker for PNS associated with adenocarcinoma. Identification of additional SKOR2 IgG positive cases will aid in categorization of associated neurological phenotype and risk of underlying malignancy.